2004
DOI: 10.1073/pnas.0405211101
|View full text |Cite
|
Sign up to set email alerts
|

Identification of a SulP-type bicarbonate transporter in marine cyanobacteria

Abstract: Cyanobacteria possess a highly effective CO2-concentrating mechanism that elevates CO 2 concentrations around the primary carboxylase, Rubisco (ribulose-1,5-bisphosphate carboxylase͞oxy-genase). This CO 2-concentrating mechanism incorporates lightdependent, active uptake systems for CO 2 and HCO 3 ؊ . Through mutant studies in a coastal marine cyanobacterium, Synechococcus sp. strain PCC7002, we identified bicA as a gene that encodes a class of HCO 3 ؊ transporter with relatively low transport affinity, but hi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
284
0
1

Year Published

2007
2007
2022
2022

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 280 publications
(287 citation statements)
references
References 30 publications
2
284
0
1
Order By: Relevance
“…and Synechocystis spp. These five C i acquisition systems comprise two inducible high-affinity HCO 3 -transporters (BCT1, Omata et al 1999;SbtA, Shibata et al 2002), a constitutive low-affinity HCO 3 -transporter (BicA, Price et al 2004), a constitutive low-affinity system to convert CO 2 into HCO 3 -(CO 2 uptake facilitator) at the NDH-1 complex located at the thylakoid membrane (NDH-1 4 , Maeda et al 2002;Price et al 2002;Shibata et al 2001), as well as an inducible high-affinity CO 2 uptake facilitator based on a modified NDH-1 complex (NDH-1 3 , Maeda et al 2002;Shibata et al 2001). All of these measures function to increase the HCO 3 -concentration in the cytosol of the cell.…”
Section: Inorganic Carbon Acquisitionmentioning
confidence: 99%
See 2 more Smart Citations
“…and Synechocystis spp. These five C i acquisition systems comprise two inducible high-affinity HCO 3 -transporters (BCT1, Omata et al 1999;SbtA, Shibata et al 2002), a constitutive low-affinity HCO 3 -transporter (BicA, Price et al 2004), a constitutive low-affinity system to convert CO 2 into HCO 3 -(CO 2 uptake facilitator) at the NDH-1 complex located at the thylakoid membrane (NDH-1 4 , Maeda et al 2002;Price et al 2002;Shibata et al 2001), as well as an inducible high-affinity CO 2 uptake facilitator based on a modified NDH-1 complex (NDH-1 3 , Maeda et al 2002;Shibata et al 2001). All of these measures function to increase the HCO 3 -concentration in the cytosol of the cell.…”
Section: Inorganic Carbon Acquisitionmentioning
confidence: 99%
“…This transporter was first described in the marine cyanobacterium Synechococcus PCC7002 (Price et al 2004) as being a low-affinity, high-flux transporter for HCO 3 -. Further characterization revealed that BicA is dependent on a sodium (Na ? )…”
Section: Inorganic Carbon Acquisitionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, the transmembrane domain structure of neither family is currently known. SLC26-related SulP genes are widely distributed among bacterial species (Felce et al 2004;Price et al 2004), in addition to the widespread expression of SLC26 genes among eukaryotic organisms (Mount et al 2004). Vertebrate SLC26 polypeptides transport a wide range of anions, including Cl − , HCO 3 − , iodide, formate, oxalate, and sulfate, and have been implicated in teleost kidney sulfate excretion and osmoregulation (Renfro et al 1999;Nakada et al 2005;Katoh et al 2006).…”
Section: Introductionmentioning
confidence: 99%
“…Vertebrate SLC26 polypeptides transport a wide range of anions, including Cl − , HCO 3 − , iodide, formate, oxalate, and sulfate, and have been implicated in teleost kidney sulfate excretion and osmoregulation (Renfro et al 1999;Nakada et al 2005;Katoh et al 2006). SulP sulfate transporters of plants and yeast have been characterized functionally, and evidence of SulP-mediated HCO 3 − transport has been demonstrated in Synechococcus species (Price et al 2004), but little other functional data on bacterial SulP proteins is available. Bacterial proteins have been important for catalyzing progress in the structure determination of polytopic membrane proteins of higher organisms.…”
Section: Introductionmentioning
confidence: 99%